Multidisciplinary approach to chronic pain from myofascial pain dysfunction syndrome: A four-year experience at a Brazilian center - Gil, Ivana A.; Barbosa, Célia Marisa Rizzatti; Pedro, Vanessa Monteiro; Alves Silverio, Kelly C.; Goldfarb, Denis Paulo; Fusco, Viviane; Navarro, Cláudia M. [UNESP] (Taylor & Francis, 1998)
Chronic pain is the major complaint of myofascial pain dysfunction syndrome (MPDS) and is a complex problem which involves physical, psychological and social aspects. The etiology of MPDS is multifactorial and the multidisciplinary approach is essential for differential diagnosis and for comprehensive treatment planning. In 1993, the Dental School of Piracicaba-UNICAMP, Brazil, opened a Center for Pain Studies (CPS), staffed by health care providers including, dentists, psychologists, physicians, physiotherapists and phonoaudiologists. The major aims of the CPS are to provide clinical care and to develop basic and applied research. Sixty-two MPDS patients had been admitted to the CPS by 1997. There were 60 females and 2 males, mean age - 32.5 years. The mean duration of chronic pain was 48 months. Pain intensity and unpleasantness were measured employing the Visual Analogue Scale. The tendency to develop stress-related diseases was assessed by the Social Readjustment Scale. There was a mean reduction of chronic pain of 69.89% and 71.78% relative to intensity and unpleasantness, respectively. The experience of clinical attendance at a multidisciplinary center showed the relevance of a team consisting of health care providers from different specialties with well-established aims, completely integrated and sensitive enough to understand the painful complaints of MPDS patients.